E-commerce Revitalization Ease Study: The Role of User-Generated Content and Swift Guanxi in Reducing Shopping Cart Abandonment to Checkout Conversion on Shopee E-Commerce - Fransiska, Helen; Heriyadi; Ramadania; Pebrianti, Wenny (Ilomata International Journal of Management, 2025)
This study analyzes the impact of User Generated Content (UGC) and swift guanxi on the intention to complete purchases in Shopee e-commerce, with trust in seller as a moderating variable, towards a background of a significant global Shopping Cart Abandonment (SCA) rate of 70.19% created for 2024. The data sample used was 230 Shopee users in Indonesia with quantitative research methods, which were analyzed using Structural Equation Modeling (SEM) and Moderated Regression Analysis (MRA) analysis for moderation testing on AMOS 22 software. The findings indicate that user-generated content and rapid guanxi significantly enhance purchase completion intention, with trust in sellers regulating these relationships. The impact of moderating to swift guanxi on the purchase completion intention is more considerable. These findings illustrate that UGC and swift guanxi can effectively reduce SCA, mainly when supported by consumer trust.